VALUE CHAIN ANALYSIS AT TUNA PROCESSED AGROINDUSTRY IN PACITAN, EAST JAVA - Irfan Miftahul Fauzi; Budi Setiawan; Anthon Efani (Socio-Economics/Agribusiness Department, 2019)
Abstract: Indonesia's economy was convener of the sea; however, the poverty of the fishermen is still high enough. The factors of management and utilization of marine fishery resources in order to improve the people's welfare are should be a significant concern. The leading commodities, tuna fish, need to be supported to increase production, processing, distribution system, diversified products. A good marketing and marketing margin distribution should be allocating a fairer on the processed tuna products. The purpose of this research is to analyze the mapping, critical factors that influence, and business value chain improvement strategies processing tuna in Pacitan. Research conducted on agro-industries processing tuna in district of Pacitan, Pacitan Regency, East Java. Sampels used are 4 fishermens, 2 traders, 2 agro-industries, 4 managers, 4 resellers, 4 retailers, and 50 consumers. Data retrieval is performed in February-March 2018. Data are analyzed using the mapping analysis, analysis of the Critical Success Factor (CSF), the analysis of governane, analysis of upgrading. Based on the analysis of the principals involved in agro-industries processing tuna are fishermens, traders, agro-industries, retailers, resellers and consumers. The party receives the smallest profit amounting to Rp 4,000 fishermen/kg. Critical factors according to agro-industries are the taste, price and quality, while the critical factor according to consumers is the taste, quality, expiration date. Factors that have a high gap are 0.49 stock and 0.55 of innovation and 0.73 of expiration. Upgrading of value chain processed tuna is process improvement by increasing production capacity, increasing the role of Marketing Manager for network marketing with branding in the tourism industry so processed tuna products widely known both national and international.